Induction of experimental autoimmune orchitis in mice: responses to elevated circulating levels of the activin-binding protein, follistatin. Issue 3 (September 2017) - Nicolas, Nour; Muir, Julie A; Hayward, Susan; Chen, Justin L; Stanton, Peter G; Gregorevic, Paul; de Kretser, David M; Loveland, Kate L; Bhushan, Sudhanshu; Meinhardt, Andreas; Fijak, Monika; Hedger, Mark P
Abstract : Experimental autoimmune orchitis (EAO) is a rodent model of chronic testicular inflammation that mimics the pathology observed in some types of human infertility. In a previous study, testicular expression of the inflammatory/immunoregulatory cytokine, activin A, was elevated in adult mice during the onset of EAO, indicating a potential role in the regulation of the disease. Consequently, we examined the development of EAO in mice with elevated levels of follistatin, an endogenous activin antagonist, as a potential therapeutic approach to testicular inflammation. Prior to EAO induction, mice received a single intramuscular injection of a non-replicative recombinant adeno-associated viral vector carrying a gene cassette of the circulating form of follistatin, FST315 (FST group). Serum follistatin levels were increased 5-fold in the FST group compared with the control empty vector (EV) group at 30 and 50 days of EAO, but intra-testicular levels of follistatin or activin A were not significantly altered. Induction of EAO was reduced, but not prevented, with mild-to-severe damage in 75% of the EV group and 40% of the FST group, at 50 days following immunisation with testicular homogenate. However, the EAO damage score (based on disruption of the blood–testis barrier, apoptosis, testicular damage and fibrosis) and extent of intratesticular inflammation (expression of inflammatory mediators) were directly proportional to the levels of activin A measured in the testis at 50 days. These data implicate activin A in the progression of EAO, thereby providing a potential therapeutic target; however, elevating circulating follistatin levels were not sufficient to prevent EAO development.